Differential effects of prophylactic iron supplementation on physiological gestational anemia and post-IDA gestational anemia: a study based on a rat model - Zhang, Zelin; Lai, Limin; Liu, Ziping; Liu, Sili; Qu, Liping; Zou, Wenjun (Frontiers in Nutrition, 2025)
ObjectiveTo observe the effects of iron supplementation on a physiological pregnancy and on pregnancy following iron deficiency anemia (IDA) caused by low-iron diet.MethodPhysiological pregnancy anemia and IDA-induced pregnancy rat models were established, and the effects of preventive iron supplementation with ferrous succinate tablets (Sulifei, SLF) and polysaccharide–iron complex (Niferex, LFN) on pregnancy ability, embryonic development, anemia indicators, and iron content and metabolic indicators were observed in the model rats.ResultAnemia markers and body iron content were decreased in physiological pregnancy rat model, accompanied by abnormal oxidative stress and iron metabolism. In post-IDA gestational rat model, these markers were even more severely aggravated. SLF and LFN intervention improved body iron content, oxidative stress, and iron metabolism-related markers in physiological pregnant rats, but did not improve anemia-related markers. After 6 weeks of pretreatment with SLF and LFN, some reproductive toxicity effects were observed. SLF and LFN intervention in post-IDA gestational rat model improved anemia markers, body iron content, and iron metabolism-related markers. There were no significant differences in reproductive parameters between the two groups. Fetal weight and the average crown–rump length per litter increased in the LFN group.ConclusionPost-IDA gestation further exacerbates iron deficiency anemia. Prophylactic iron supplementation can significantly improve physiological iron deficiency and iron metabolism during pregnancy but cannot improve iron deficiency anemia. In contrast, iron supplementation can significantly improve iron deficiency anemia in post-IDA gestation. To prevent or treat pregnancy complicated by IDA, iron supplementation is recommended either before the onset of IDA or after pregnancy.